Quelques elements sur less effectifs d'elephants au parc national du Niokolo Koba (annee 2000) - Mauvais, Geoffroy (Pachyderm, 2001)
Ground and aerial surveys undertaken during the first half of 2000 confirm that elephant numbers in Niokolo Koba NP are very low, and no animals were noted near the Gambia River which is considered an important dry season water source. Earlier survey results noted 150 during a one day survey in May 1969 in the vicinity of the Gambia River, 200 were estimated to be present in a May 1970 survey, about 50 in 1985, and 30 in 1993. The ground survey between April and July 2000 suggested 4 animals (2 adults and 2 juveniles) were present in the transected area within the Park's southern region. Only 4 animals (2 adults, one male and one female and two juveniles were observed duirng 21 hours of aerial survey time. Results suggest that less than 30 elephant may be present in the area and the future for elephant here is very uncertain. Poaching has been a problem for many years and a skull and bones seen during the survey suggest it may casue for concern.